LncRNA GAS5 suppresses TGF-β1-induced transformation of pulmonary pericytes into myofibroblasts by recruiting KDM5B and promoting H3K4me2/3 demethylation of the PDGFRα/β promoter - Yichun Wang; Diyu Chen; Han Xie; Shuhua Zhou; Mingwang Jia; Xiaobo He; Feifei Guo; Yihuan Lai; Xiao Xiao Tang (BMC, 2023)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a condition that may cause persistent pulmonary damage. The transformation of pericytes into myofibroblasts has been recognized as a key player during IPF progression. This study aimed to investigate the functions of lncRNA growth arrest-specific transcript 5 (GAS5) in myofibroblast transformation during IPF progression. Methods We created a mouse model of pulmonary fibrosis (PF) via intratracheal administration of bleomycin. Pericytes were challenged with exogenous transforming growth factor-β1 (TGF-β1). To determine the expression of target molecules, we employed quantitative reverse transcription-polymerase chain reaction, Western blotting, and immunohistochemical and immunofluorescence staining. The pathological changes in the lungs were evaluated via H&E and Masson staining. Furthermore, the subcellular distribution of GAS5 was examined using FISH. Dual-luciferase reporter assay, ChIP, RNA pull-down, and RIP experiments were conducted to determine the molecular interaction. Results GAS5 expression decreased whereas PDGFRα/β expression increased in the lungs of IPF patients and mice with bleomycin-induced PF. The in vitro overexpression of GAS5 or silencing of PDGFRα/β inhibited the TGF-β1-induced differentiation of pericytes to myofibroblasts, as evidenced by the upregulation of pericyte markers NG2 and desmin as well as downregulation of myofibroblast markers α-SMA and collagen I. Further mechanistic analysis revealed that GAS5 recruited KDM5B to promote H3K4me2/3 demethylation, thereby suppressing PDGFRα/β expression. In addition, KDM5B overexpression inhibited pericyte-myofibroblast transformation and counteracted the promotional effect of GAS5 knockdown on pericyte-myofibroblast transformation. Lung fibrosis in mice was attenuated by GAS5 overexpression but promoted by GAS5 deficiency. Conclusion GAS5 represses pericyte-myofibroblast transformation by inhibiting PDGFRα/β expression via KDM5B-mediated H3K4me2/3 demethylation in IPF, identifying GAS5 as an intervention target for IPF.